Phytochemical and Pharmacological Evaluation of the Residue By-Product Developed from the Ocimum americanum (Lamiaceae) Postdistillation Waste - Izabela Jasicka-Misiak; Mariia Shanaida; Nataliia Hudz; Piotr Paweł Wieczorek (Foods, 2021)
The yield of essential oils in plants is not high and postdistillation wastes rich in phenolic compounds could be used to enhance the profitability of essential oil-bearing plants. The aim of the study was to evaluate polyphenols in a dry extract obtained from the postdistillation waste of the American basil (Ocimum americanum L.) herb, and to conduct the screening of its pharmacological activities. Rosmarinic acid, caffeic acid and rutin were identified in the extract using high-performance thin-layer chromatography. The high-performance liquid chromatography analysis found the presence of a plethora of polyphenols in the extract. Rosmarinic acid, luteolin-7-O-glucoside and rutin were as the main compounds. The total phenolic content in the extract was 106.31 mg GAE/g and free radical scavenging activity against 2,2-diphenyl-1-picrylhydrazyl evaluated as IC50 was 0.298 mg/mL. The tested extract dose-dependently decreased the paw edema in rats, suggesting its potent anti-inflammatory property. The acute toxicity study indicates its safety. Thus, the O. americanum hydrodistilled residue by-product is the promising source of biologically active compounds with significant antioxidant and anti-inflammatory effects.